Root hairs improve root penetration, root–soil contact, and phosphorus acquisition in soils of different strength - Haling, Rebecca E; Brown, Lawrie K; Bengough, A. Glyn; Young, Iain M; Hallett, Paul D; White, Philip J; George, Timothy S (Journal of experimental botany, 2013)
Root hairs are a key trait for improving the acquisition of phosphorus (P) by plants. However, it is not known whether root hairs provide significant advantage for plant growth under combined soil stresses, particularly under conditions that are known to restrict root hair initiation or elongation (e.g. compacted or high-strength soils). To investigate this, the root growth and P uptake of root hair genotypes of barley, Hordeum vulgare L. (i.e. genotypes with and without root hairs), were assessed under combinations of P deficiency and high soil strength. Genotypes with root hairs were found to have an advantage for root penetration into high-strength layers relative to root hairless genotypes. In P-deficient soils, despite a 20% reduction in root hair length under high-strength conditions, genotypes with root hairs were also found to have an advantage for P uptake. However, in fertilized soils, root hairs conferred an advantage for P uptake in low-strength soil but not in high-strength soil. Improved root–soil contact, coupled with an increased supply of P to the root, may decrease the value of root hairs for P acquisition in high-strength, high-P soils. Nevertheless, this work demonstrates that root hairs are a valuable trait for plant growth and nutrient acquisition under combined soil stresses. Selecting plants with superior root hair traits is important for improving P uptake efficiency and hence the sustainability of agricultural systems.